Analysis of junior high school students’ algebraic reasoning abilities in solving problems viewed from the perspective of Adversity Quotient (AQ) - Diyah, Fima Hayu Ning; Shodikin, Ali (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study is motivated by the relatively low algebraic abilities of Indonesian students, particularly in transforming contextual problems into formal mathematical representations, as highlighted in recent mathematics education findings . Beyond cognitive factors, students’ success in overcoming such difficulties is strongly influenced by their mental resilience, known as Adversity Quotient (AQ). Therefore, this research aims to describe junior high school students’ algebraic reasoning abilities in problem-solving from the perspective of AQ. A descriptive qualitative approach was employed, involving three ninth-grade students representing each AQ category: climber, camper, and quitter. The subjects were selected through stratified purposive sampling based on the results of the Adversity Response Profile (ARP) questionnaire. Data were collected using written algebraic reasoning tasks integrating social arithmetic and two-variable linear inequalities, as well as in-depth semi-structured interviews. Data analysis followed the Miles, Huberman, and Saldaña model, including data condensation, data display, and conclusion drawing. The findings indicate significant differences in algebraic reasoning across AQ types. Climber students successfully demonstrated all stages of algebraic reasoning—pattern seeking, pattern recognition, and generalization—supported by persistence and adaptive strategies. Camper students showed adequate ability in identifying and recognizing patterns but were limited in formal representation and generalization. In contrast, quitter students experienced substantial difficulties at almost all stages, reflecting low persistence. These results confirm that AQ plays a crucial role in shaping students’ algebraic reasoning and problem-solving performance.